It's not as bad as you think: menopausal representations are more positive in postmenopausal women - Lydia Brown; Valerie Brown; Fiona Judd; Christina Bryant (Taylor & Francis Group, 2018)
Introduction: The menopausal transition is associated with underlying hormonal changes that can contribute to a range of physical and emotional symptoms. Psycho-social factors including attitudes and internal representations play a central role in women's experience of the menopause, but very little is known about how representations might differ across menopausal stages. Methods: A sample of 387 women aged 40-60 completed a postal questionnaire that included the menopausal representations questionnaire, the emotional representation subscale adapted from the illness perception questionnaire, and data on menopausal status. Results: Significant differences across menopausal stages were found for both cognitive [F(2, 381) = 4.32, p < .05, η2 = 0.022], and emotional [F(2, 381) = 9.70, p < .01, η2 = 0.048] menopausal representations. Postmenopausal women had a significantly more positive cognitive representations of the menopause relative to perimenopausal women (standardised mean difference = 0.25, p > .05). Postmenopausal women held a significantly more positive emotional representation of the menopause than both premenopausal (standardised mean difference = 0.56, p < .05) and perimenopausal (standardised mean difference = 0.43, p < .05) women. Discussion: Women's emotional and cognitive representations of the menopause are more positive among postmenopausal women, compared to women in the late premenopausal stage. This is consistent with the affective forecasting theory, which proposes the tendency to overestimate the intensity and duration of emotional reactions to future events. Given the association between representations and bothersomeness of menopausal symptoms, clinicians should educate women about their expectations, and challenge their negative beliefs about the menopause.